Factors Causing Early Marriage - Aliyah, Aliyah; Octhatriani, Noumy; Wulandari, Arditha; Mareta Undaryat, Yeti (Riviera Publishing, 2024)
Early marriage is a social phenomenon that still occurs in many countries, including Indonesia. According to Adam A (2020), marriage is a ceremony carried out by two people to formalize a marriage bond based on religious, legal, and social norms. However, early marriage is often triggered by various factors such as cultural norms, poverty, and pregnancy out of wedlock. Law of the Republic of Indonesia No. 16 of 2019 concerning Marriage regulates the minimum age limit for marriage, which is 19 years for men and women, although early marriage is still taking place in some regions. This study uses a qualitative approach by examining various literature and statistical data related to early marriage. The results of the study show that early marriage can be at high risk to the reproductive, psychological, and quality of life of young couples. Negative impacts that often arise include pregnancy complications, divorce risks, and emotional disturbances for adolescents who are not ready to take on the role of husband or wife. On the other hand, some of the positive impacts found are the reduction of the family's economic burden and the learning of responsibility. To reduce the rate of early marriage, there needs to be increased education, socialization about its negative impacts, and stricter law enforcement. Therefore, there needs to be collaboration between the government, the community, and educational institutions to prevent early marriage in Indonesia.